Pemanfaatan tepung putak (Corypha utan) sebagai pakan pengganti tepung dedak (Oryza sativa) terhadap pertumbuhan ikan bandeng (Chanos chanos Forskal) - Dionesia A Hanmima; Yulianus Linggi; Yudiana Jasmanindar (Nusa Cendana University, 2021)
This research aims to determine the growth of milkfish fed with putak flour formulation as a substitute for bran and to determine the optimal level of substitution for milkfish growth which was carried out for 2 months in the implant ponds of the Fisheries Service, Dualaus Village, KakulukMesak sub-district, Belu regency. This study used a completely randomized design (RAL, 5r, 3t). The treatments tested were treatment A (100% bran flour in feed), treatment B (25% putak flour, 75% bran flour in feed), C treatment (50% putak flour, 50% bran flour in feed), treatment D ( 75% putak flour, 25% bran flour in feed) and E treatment (100% putak flour in feed). The ANOVA shows that the treatment is significantly different on absolute growth, significantly different on specific growth and not significantly different on survival. The highest weight growth was found in treatment E (13.33g), followed by D (11.53 g), treatment A (10.5g), treatment B (9.53g) and treatment C (8.3g). The highest specific growth was treatment E (1.61g), followed by treatment D (1.59 g% / day), treatment A (1.07 g% / day), treatment B (0.99 g% / day) and treatment C (0.89 g% / day). day). The highest survival rate was found in treatment A (96.6%), followed by treatment E (93.3%), treatment B and D (90%), treatment C (0.89%). The results of this study provide the conclusion that the optimal level of putak flour substitution to bran flour by giving 100% putak flour in feed can increase the growth of milkfish. Key words: Growth, Milkfish, Sago Flour, Survival Rate.